Heart of a Hoosier : A Year of Inspiration from IU Men's Basketball - Duduit, Del, 1966-; Adams, Michelle Medlock (Book collections on Project MUSE., 2021)
"Five NCAA Championships, 22 Big Ten Conference Championships-this is the candy-striped legacy of the Indiana University men's basketball team. In its 120-year history, Indiana basketball has become a giant in college basketball and earned a legion of fans. In Heart of a Hoosier: A Year of Inspiration from IU Men's Basketball, authors Del Duduit and Michelle Medlock Adams show readers how the famous moments and personalities of the Indiana Hoosiers can inspire them to reach for success, overcome adversity, be a great team member, and more. Readers will be inspired by a year's worth of stories featuring fierce rivalries with Purdue and Kentucky and legendary players and coaches such as Steve Alford, Isiah Thomas, Calbert Cheaney, George McGinnis, Branch McCracken, and Bobby Knight. Heart of a Hoosier will entertain and motivate every fan who bleeds Cream & Crimson. Relive the triumphs, groan at the losses, and revel in great traditions!"--